2021
DOI: 10.3390/app11041462
|View full text |Cite
|
Sign up to set email alerts
|

Development of Add-On Planar Translational Driving System for Aerial Manipulation with Multirotor Platform

Abstract: We propose an add-on planar translational driving system (ATD) which can be equipped on a multirotor platform for aerial manipulation. The device is lightweight and consists of three ducted fans controlled via an on-board CPU. It uses a simple control method and enables a multirotor to perform positioning and generate force in two dimensions while keeping the airframe horizontal. By translating the multirotor without changing attitude, it can more smoothly and easily perform many types of aerial manipulation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The system generates the required torque, by landing on valve, disarming the UAV's propellers, and utilizing the forces generated by the thrust vectoring device. With the previous research in [16] we showed the effectiveness of an add-on thruster system for UAVs, which generated horizontal forces independent from the multirotor UAV's propellers. However, due to the fixed configuration and orientation of the additional actuators, the use of this system was limited to translational movement.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The system generates the required torque, by landing on valve, disarming the UAV's propellers, and utilizing the forces generated by the thrust vectoring device. With the previous research in [16] we showed the effectiveness of an add-on thruster system for UAVs, which generated horizontal forces independent from the multirotor UAV's propellers. However, due to the fixed configuration and orientation of the additional actuators, the use of this system was limited to translational movement.…”
Section: Introductionmentioning
confidence: 66%
“…In this study, our previous research in [16] has been enhanced with thrust vectoring capabilities. The original system allowed for a commercial UAV to move in a planar motion, i.e., without changing the pitch and roll of its frame.…”
Section: System Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to increase the capability of conventional multi-rotors to generate forces along the horizontal plane, required in many contact-based inspection operations, the authors in [3] describe an add-on mechanism for multi-rotors, consisting of three ducted fans arranged in a Y-shaped structure that can be easily integrated in different types of multirotors, in such a way that the horizontal thrust allows the decoupling of the translational control from the attitude control. The developed prototype demonstrates how a relatively simple concept design can extend the functionalities and control capabilities of aerial robots.…”
Section: Contribution and Advancesmentioning
confidence: 99%